Effects of Sulfonylureas Treatment on Apoptosis, Total Superoxide Dismutase activity and Some Biochemical Parameters in Type 2 Diabetic Patients - Noor Khalid Zaidan1 , Perry H. Saifullah2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The purpose of this analysis was to evaluate the the influence of anti-diabetic drugs (sulfonylureas) in type two diabetic patients and the risk of developing diabetes complications related to kidney disease (Diabetic Nephropathy ) compared to healthy subjects by measuring influence of some apoptosis factors ( serum Tumor necrosis factor soluble Receptor-1(TNF-R1) and TNF-related apoptosis-inducing ligand receptor-2 (TRAIL-R2)) concentrations , Serum Small mothers against decapentaplegic (Smad1 ) as anew marker of diabetic nephropathy (DN) ,Superoxide dismutase concentration (SOD) ,Glycated hemoglobin (HbA1c%) , Fasting plasma glucose (FPG) ,insulin concentration , insulin resistance (IR) ,urea and creatinine .A samples of convenience composed of 17 type 2 diabetic patients with sulfonylureas monotherapy and 17 normal subjects above the age of 40 years were recruited . Age ,duration of disease and body mass index (BMI) was created. The mean levels of Smad1 and TRAIL- R2 in diabetics with sulfonylureas treatment , they were significantly higher compared to control subjects, while the means of SOD have low level in diabetic subjects , and the mean levels of TNF-R1 and IR were non-significant in diabetic with Sulfonylureas treatment compared to control subjects.